The Influence of Job Stress, Transformational Leadership, and Knowledge Sharing Toward Innovative Work Behavior at the Tourism Office of the Province of West Sumatra - Esa Lovena; Yulihasri Yulihasri; Hendra Lukito (International Journal Labs, 2023)
Entering the era of globalization with various challenges that exist requires us to be able to adjust. One way to be able to adjust to dynamic changes is to innovate. Innovation is changing for the better. As one of the agencies that require innovation is the West Sumatra Tourism Office in order to boost the Indonesian economy, one of which is in the tourism sector. This study aims to examine and build a conceptual model of the influence of Job Stress, Transformational Leadership, and Knowledge sharing towards innovative work behavior on ASN employees of the West Sumatra Provincial Tourism Office. This study used a non-probability sampling technique with a sample used of 58 ASNs through the distribution of questionnaires. The data analysis technique used is path analysis using Smart PLS software. Research hypothesis testing uses T-statistical tests obtained through the bootstrapping process. The results show that Job stress, Transformational Leadership are not able to directly affect innovative work behavior. Job stress affects knowledge sharing directly. Transformational leadership affects Knowledge sharing, and knowledge sharing affects innovative work behavior. The West Sumatra Tourism Office has not been able to implement Innovative work behavior without going through knowledge sharing. This is evidenced by the absence of a direct influence of job stress and transformational leadership on Innovative work behavior. This is because the employees of the West Sumatra Tourism Office have been working for a long time and have more experience and the ability to manage job stress. So that the existence of job stress does not affect the innovative work behavior of employees because they have a high ability to manage job stress on Innovative work behavior.